Wim Crouwel : modernist - Huygen, Frederique; Crouwel, Wim (Eindhoven : Lecturis Publishers, 2015)
"A new, detailed monograph about Wim Crouwel, graphic designer and exhibition designer who defined the look of post war Holland with his studio Total Design. His modernism was reflected in countless posters and catalogues for the Stedelijk Museum, in stamps and experimental work like a sensational computer alphabet. In the seventies Crouwel evoked a lot of criticism but nowadays he is seen as a cult figure and an inspiration for many. The book is richly illustrated and shows us very much of his fine works. The text focuses on his career and views, gives informative backgrounds on his work, and places it in the right context"--Publisher's website.
Preface -- Wim Crouwel: modish, modern, modernist -- Biography in pictures -- The third dimension -- Signs and elements -- 1956-1964: the Van Abbe Museum and NKS -- Circles and spirals -- Constructivist: Liga, Switzerland and Ulm -- Company printing -- Total design 1963-1972 -- Calendars -- The Stedelijk Museum -- Technology, systems and patterns -- TD 1973-1985: Crouwel criticized -- Postage stamps -- Crouwel in the media: a dogmatist full of contradictions -- Museum director, design commissioner and museum designer -- Comeback and revival -- Texts by Crouwel -- CV Crouwel -- Bibliography and sources -- Index.
boek
Keywords: Crouwel, Wim -- Criticism and interpretation; Graphic artists -- Netherlands -- History; Graphic design (Typography) -- Netherlands -- History; Crouwel, Wim; Graphic artists; Graphic design (Typography); Netherlands; Crouwel, Wim, -- 1928-; Gebrauchsgrafik; Textgestaltung; Criticism, interpretation, etc; History